Stakeholders ‘Preparedness for ‘the Big One’ Earthquake: the Case of Greater Manila and other Vulnerable Provinces - Ojurongbe, Samuel Ayodele (MultiTech Publisher, 2024)
The ‘Big One’ earthquake has been predicted to occur in the Philippines at any time. Manila has been forecast to experience a 7.2-magnitude earthquake that would result in several fatalities. The country has developed its management structures at the local, provincial and international levels. However, questions have been asked on whether these measures are enough to show readiness for ‘The Big One’ earthquake. Literature reveals that a long-term planning and clear cut resource mobilization for disaster management is still lacking. Policies have also failed to spell out what is required of the marginalized, civil society and relevant institutions. The review extends with a tabulation of possible theoretical and conceptual lenses to guide the study.